2017
DOI: 10.1002/etc.3983
|View full text |Cite
|
Sign up to set email alerts
|

Hematological indices of injury to lightly oiled birds from the Deepwater Horizon oil spill

Abstract: Avian mortality events are common following large-scale oil spills. However, the sublethal effects of oil on birds exposed to light external oiling are not clearly understood. We found that American oystercatchers (area of potential impact n = 42, reference n = 21), black skimmers (area of potential impact n = 121, reference n = 88), brown pelicans (area of potential impact n = 91, reference n = 48), and great egrets (area of potential impact n = 57, reference n = 47) captured between 20 June 2010 and 23 Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 46 publications
3
31
1
Order By: Relevance
“…Our results support our hypothesis that RBGUs develop some degree of anemia secondary to external oil exposure, similar to other avian species. The anemia seen in oiled RBGUs falls within the range of anemia found in externally oiled birds sampled shortly after the Deepwater Horizon oil spill which had on average a 4–19% lower PCV than non-oiled birds (40). Oiled RBGUs may have had a milder anemia compared to some of the birds sampled after Deepwater Horizon due to their easy access to nutritious, oil-free food, and limited need to expend energy foraging.…”
Section: Discussionsupporting
confidence: 53%
“…Our results support our hypothesis that RBGUs develop some degree of anemia secondary to external oil exposure, similar to other avian species. The anemia seen in oiled RBGUs falls within the range of anemia found in externally oiled birds sampled shortly after the Deepwater Horizon oil spill which had on average a 4–19% lower PCV than non-oiled birds (40). Oiled RBGUs may have had a milder anemia compared to some of the birds sampled after Deepwater Horizon due to their easy access to nutritious, oil-free food, and limited need to expend energy foraging.…”
Section: Discussionsupporting
confidence: 53%
“…Plumage phase differences between oiled and non-oiled birds could indicate stressors associated with oil exposure, rehabilitation, and/or tracking equipment. A wide range of debilitating sublethal impacts following oil exposure have been previously described [4, 8, 13, 26], but impacts on subsequent feather replacement have not been specified. Our finding that post-spill pelicans moved through the prebasic hindneck plumage transition (from brown to white feathering) at a rate insignificantly different from the general population indicated that this molt process proceeded normally despite the trauma of the spill event.…”
Section: Discussionmentioning
confidence: 99%
“…Sublethal effects of oil spills on seabirds may result in failure to thrive despite plumage restoration and other rehabilitation efforts [4, 9, 10]. Such impacts are difficult to measure once birds are released but may play an important role in population restoration [1113].…”
Section: Introductionmentioning
confidence: 99%
“…To offset this thermal loss, birds normally increase their basal metabolic rate, which can deplete stored body fat and possibly starvation. Ingestion of oil can lead to anemia (Leighton 1993;Yamato et al 1996, Fallon et al 2017 which can affect aerobic performance and since all these three species are migratory, any reduction in oxygen carrying capacity during flight is likely to have adverse effects. In addition, because loons and gannets are divers, reduction in oxygen carrying capacity could compromise foraging abilities.…”
Section: Potential Fate Of Oiled Birdsmentioning
confidence: 99%
“…Ingestion of oil exposes birds to polycyclic aromatic hydrocarbons (PAHs), highly toxic components of crude oil and known carcinogens (Albers 2006). In addition, PAH exposure is linked to numerous pathological effects, such as anemia, gut damage, renal and liver damage, alterations in immune and endocrine function, and weight loss (Peakall et al 1981;Fry and Lowenstine 1985;Leighton 1993;Jenssen 1994;Yamato et al 1996;Briggs et al 1997;Burger and Tsipoura 1998;Trust et al 2000;Paruk et al 2016;Fallon et al 2017;Harr et al 2019). Exposure to sublethal oiling levels puts more birds at risk, potentially leading to lower fitness (Golet et al 2002;Alonso-Alvarez et al 2007).…”
Section: Introductionmentioning
confidence: 99%